Epitypification Carex bolanderi (Cyperaceae) - Reveal, James L.; Naczi, Robert F.c.; Zika, Peter F. (Phytotaxa, 2014)
With the description of Carex infirminervia Naczi (in Naczi et al. 2002: 528) and the summation of Carex sect. Deweyanae (Tuckerman ex Mackenzie 1913: 352) Mackenzie (1931: 114) by Naczi (in Naczi 2002: 321–325), a recent summary of Pacific Northwest sedges (Wilson et al. 2008: 106–107), and the new Jepson Manual (Zika et al. 2012: 1322), the circumscription of C. bolanderi Olney (1868: 393) is now firmly established. As such, C. bolanderi occurs from southern British Columbia to southern California east to Montana, Utah and New Mexico, and then south in the Sierra Madre Occidental through Chihuahua to northern Durango, Mexico. Previous usage of C. bolanderi was somewhat confused both as to its circumscription and to its distribution because of the inclusion of some specimens of C. infirminervia as in the cases of Munz (1959: 1443, 1974: 887) and Mastrogiuseppe (1993: 1122), or when it was included in C. deweyana Schweinitz (1824: 65; e.g., Cronquist 1969: 261, 1977: 158, Taylor 1983: 102).